2018
DOI: 10.1017/s0007114518000351
|View full text |Cite
|
Sign up to set email alerts
|

Is there any difference between the iodine statuses of breast-fed and formula-fed infants and their mothers in an area with iodine sufficiency?

Abstract: Despite substantial progress in the global elimination of iodine deficiency, lactating mothers and their infants remain susceptible to insufficient iodine intake. This cross-sectional study was conducted to compare iodine statuses of breast-fed and formula-fed infants and their mothers at four randomly selected health care centres in Tehran. Healthy infants <3 months old and their mothers were randomly selected for inclusion in this study. Iodine was measured in urine and breast milk samples from each infant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(87 reference statements)
2
3
1
Order By: Relevance
“…However, a higher mean age, lower breast-feeding rates and higher iodine intake from complementary foods in the two studies may explain the differences compared with our results. Unlike our results, several studies have not found an association between infant UIC and breast-feeding status (41)(42)(43)(44) . However, compared with our study, these studies reported adequate infant UIC and higher BMIC.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a higher mean age, lower breast-feeding rates and higher iodine intake from complementary foods in the two studies may explain the differences compared with our results. Unlike our results, several studies have not found an association between infant UIC and breast-feeding status (41)(42)(43)(44) . However, compared with our study, these studies reported adequate infant UIC and higher BMIC.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, both children’s UIC and iodine intake were positively associated with all markers of maternal iodine nutrition (BMIC, UIC, and estimated iodine intake). This supports the importance of maternal iodine nutrition in providing sufficient iodine intake in young children and is also consistent with the findings of other studies [ 6 , [39] , [40] , [41] ].
FIGURE 3 Box plot of children’s dietary iodine intake by 24-HRs, stratified by the 3 age groups.
…”
Section: Discussionsupporting
confidence: 92%
“… Association between BMIC (blue) and maternal UIC (orange) and/or infant UIC (yellow) from cross-sectional studies conducted in lactating mothers and their breastfed infants. Data points show median BMIC, median maternal UIC, and median infant UIC obtained in mother-infant pairs (sample size, n = 52-739) ( 112 , 145 , 146 , 166 , 167 , 203 , 204 , 211 , 246-258 ). The dashed lines indicate current thresholds for the median BMIC and median UIC above which the iodine intake is considered adequate ( 21 ).…”
Section: Iodine In Human Milkmentioning
confidence: 99%
“…Studies conducted in formula-fed infants report adequate median UIC ( 204 , 210 , 352 , 353 ), but data are limited. Some studies report lower median UIC in formula-fed infants compared to breastfed infants ( 210 , 352 , 354 ), whereas other studies observe no difference ( 204 , 353 ). The iodine intake depends on the iodine content in formula milk and the BMIC.…”
Section: Biomarkers Of Iodine Statusmentioning
confidence: 99%